Heat and Mass Transfer Due To Double Diffusive Mixed Convection in a Parallel Plate Reactor in Presence of Chemical Reaction and Heat Generation - Parvin, Salma; Alim, M.A; Hossain, N.F (International Journal of Chemical and Process Engineering Research, 2015)
The present paper aims to analyze numerically the heat and mass transfer for laminar double-diffusive mixed convection flow in a parallel plate reactor with heat generation and chemical reaction. The reactant fluid enters from the left inlet and exits from the right outlet. All solid walls of the reactor are assumed to be thermodynamically isolated. After entering the reactor, the fluid passes four heated cylinder. Two-dimensional continuity, momentum, energy and concentration equations govern the developed mathematical model. Galerkin finite element method with triangular grid discretization system is used to solve the governing non-dimensional equations. The aim of the investigation is to illustrate the effects of the energy expelled during the reaction, on velocity, the thermal field and concentration of the heat sensitive chemical. Numerical simulations are conducted for different combinations of chemical reaction parameter and heat generation parameter. Results are presented in terms of streamlines, temperature and concentration distributions. The results reveal that the heat and mass transfer rate strongly depend on the mentioned parameter.